The Role of Islamic Religious Education Teachers in Increasing the Spiritual Intelligence of Students at Muhammadiyah Pakem High School, Yogyakarta - Dicky Darmawansa; Sutarman (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The background of this research is that the condition of education in Indonesia is currently very worrying and quite a few disciplinary violations are found in schools, such as students still skipping religious activities (Dhuha prayers, midday prayers, Asr prayers), drunkenness, reckless driving and online gambling. as well as the current bad impacts of globalization which tend to attack and tempt students in various schools in Indonesia. The role of Islamic religious education teachers is very much needed to be able to increase the spiritual intelligence of their students. Apart from having intellectual intelligence, students are expected to have spiritual intelligence, with this, students are able to develop themselves into complete human beings by always thinking positively by responding to every incident. Increasing students' spiritual intelligence is one of the roles of teachers as educators. In this case, it is not uncommon for a teacher to experience obstacles, so the teacher must play an active role in increasing spiritual intelligence with the aim of implementing the role of the teacher optimally in school. The purpose of this research is to find out what students' spiritual intelligence is, to find out what the teacher's role is in increasing students' spiritual intelligence, and to find out what supporting and inhibiting factors are in increasing students' spiritual intelligence. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interviews and documentation. The data analysis techniques used are data reduction, data display and conclusion drawing. The results of this research indicate that the role of teachers in increasing the spiritual intelligence of class X students at SMA Muhammadiyah Pakem Yogyakarta is quite optimal. The teacher's role as a guide, motivator and counselor is starting learning by always reciting the Al-Qur'an, guidance in reading, writing and memorizing the Al-Qur'an, Dhuha in congregation, midday in congregation, Asr in congregation, dhikr and prayer together after prayer, increasing IMTAQ, for male students, every Friday they take turns at the call to prayer and the Friday sermon, while for female students they take turns at the kultum after midday prayers Monday to Thursday and the target is to memorize 2 (two) Juz for graduation. Supporting factors for the teacher's role in increasing students' spiritual intelligence are the teacher's role, teacher and parent communication, and the student's environment. Meanwhile, the inhibiting factors are the students' different backgrounds, the environment and unstoppable modern technology that displays negative content.